Circular dichroism as a means to follow DNA gymnastics: on the shoulders of giants - M. Mills; C. Lin; M. Chauhan; H.H. Klump (South African Journal of Science)
This is the first report of DNA stem-loops self-assembled by 'foot-loop' interactions into either two-dimensional strings or three-dimensional spirals, distinguished by circular dichroism spectroscopy. All subunits are linked by cooperative Watson-Crick hydrogen bonds.